Strengthening climate services for the food security sector - Hansen, James; Fara, Katiuscia; Milliken, Kathryn; Boyce, Clement; Chang’a, Ladislaus; Allis, Erica (2018)
The Global Framework for Climate Services (GFCS) enables vulnerable sectors and populations to better manage climate variability and adapt to climate change. How? By developing and incorporating science-based climate information into planning, policy and practice. The GFCS places the decision context and information needs of “users” at the centre of the design process. The development of such climate services alters the dynamic between the “user” and the “provider,” valuing each actor's knowledge and engaging them both in a co-production process. This approach challenges the conventional linear supply chain for weather and climate information, in which data are generated, information produced, a product designed, and handed over to the user for consumption, without a real understanding of whether this information is useful for decision-making.